Telephones, music and history: From the invention era to the early smartphone days. (December 2021) - Behrendt, Frauke
This article focusses on the musical history of the telephone, an aspect of telephonic history that is often overlooked and has not yet received systematic academic attention. The article is structured around two musical themes of telephonic history: (1) public performances of telephones as musical instruments and (2) the telephone network as musical instrument. Two historic periods are considered for both themes, (a) the late 1800s/early 1900s and (b) the late 2000s. The article's approach draws loosely on media historic and media archaeologic perspectives to analyse existing material about telephone history (with a musical focus) alongside empirical field work on the musical use of mobile phones in the late 2000s. The results contribute to debates regarding the 'newness' of media, and to sound studies approaches to media histories. The article shows how the theme of the musical telephone has been re-occurring but often overlooked throughout its history, and also sketches out a future research agenda. The article contributes a new understanding of the musical uses of the telephone across history, relevant for both understanding contemporary uses of telephone technologies such as smartphones and the Internet of Things, and for a richer understanding of historic telephone uses.